Intra-party conflict at grassroots: Party-councillor ideological congruence in Croatia. (September 2019) - Kukec, Marko
Party-councillor ideological congruence reinforces party linkages with local voters and credibility of councillors as future party elites. This contribution examines the role of career motivations and selective incentives, as well as party branch characteristics in forming party-councillor congruence. The empirical analysis draws on the original survey of Croatian local councillors. The results find councillors with progressive ambition and those exposed to intra-branch competition reporting higher levels of ideological congruence with their parties, while no effect was found for holders of upper level party positions. Branch power has the opposite effect from expected. Party grassroots shape ideologically congruent professional politicians, but this function is challenged by shrinking supply of candidates.